Identification, expression and enzyme activity of the group III sPLA2s in Cyprinus carpio L. Issue 1 (26th May 2021) - Xu, Yuxin; Li, Hongxia; Xu, Dihui; Li, Jianlin; Yu, Fan; Wang, Meiyao; Wang, Qin; Wu, Yunsheng; Zhang, Qiyuan; Tang, Yongkai; Yu, Juhua
Abstract: Five group III secreted phospholipase (pla2g3s) homologous genes located on different linkage groups were identified from common carp ( Cyprinus carpio ), which we named Ccpla2g3a1, Ccpla2g3a2, Ccpla2g3b, Ccpla2g3c1 and Ccpla2g3c2 . The five genes encode 530, 525, 461, 752 and 753 amino acids, respectively. Sequence analysis showed that the Ccpla2g3a s contain seven exons and the others contain four exons. Synteny analysis of fish pla2g3s indicated that pla2g3a and pla2g3b were from the same ancestor gene, and Ccpla2g3a 1, Ccpla2g3a 2, Ccpla2g3c 1 and Ccpla2g3c 2 were from the specific genome duplication of common carp. Due to the significant variation of the pla2g3bs from common carp and zebrafish ( Danio rerio ), they formed a separate group in the phylogenetic tree. The tissue distributions of Ccpla2g3 s coincided with their expression profiles during the embryo stages. The expression levels of Ccpla2g3a s and Ccpla2g3c s were low at the embryo stages, and they were abundant in the liver and brain, respectively, whereas the expression of Ccpla2g3b was high at 0.5 h after fertilization and in the ovary. We obtained three soluble recombinant proteins of the bee venom‐like PLA2 (BVLP) from Ccpla2g3 and evaluated their PLA2 enzyme properties. The optimum pHs of MBP‐a1‐BVLP, MBP‐b‐BVLP and MBP‐c1‐BVLP were 7.5, 7.0 and 8.0, respectively, and specific activities were 7.68 ± 0.66, 4.155 ± 0.158 and 1.93 ± 0.05 U μmol –1, respectively. The K d for Ca 2+ of MBP‐b‐BVLP was the lowest (2.6 μM), whereas the values for both MBP‐a1‐BVLP and MBP‐c1‐BVLP were about 15 μM. The K m values of three proteins ranged from 31.9 to 41.91 μM.